A lifeline in the dark: Breaking through the stigma of veteran mental health and treating America's combat veterans. Issue 5 (11th January 2020) - Botero, Gabriel; Rivera, Nilsa I.; Calloway, Shakeya C.; Ortiz, Pedro L.; Edwards, Emily; Chae, John; Geraci, Joseph C.
Abstract: For generations, veterans have answered the call to service and served their country honorably and with distinction. Unfortunately, the consequences of combat cause many veterans to struggle with life after the military and with readjustment/reintegration into civilian life. Today more than ever, there are a multitude of resources, education, and treatment options for combat veterans. For mental and physical health providers, business leaders, and other professionals who work with veterans, it is of the upmost importance that they learn about programs around them that are successful in treating veterans. The current article reviews two U.S. Department of Veterans Affairs nationwide programs—the Readjustment Counseling Service/Vet Center and Veteran Cultural Competence Training—designed to decrease mental health stigma for veterans and to increase veteran engagement with mental health services. These programs highlight the importance of being aware of the culture within military systems, being aware of personal biases, and fostering an environment of genuineness, safety, and nonjudgmental empathy. In doing so, these programs are successful in reducing the unspoken power of stigmatization; they effectively reach out to veterans in need, providing a lifeline in the dark.